Index Card Match dalam Pembelajaran Mufradat di Madrasah Ibtidaiyah - Taufik, Taufik; Mas'ud, Sulthon; Fuad Erfansyah, Nasrul; Purnamasari, Santri (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Purpose- The purpose of this article is to explain the results of research on how to use the Index Card Match strategy in learning Arabic subjects and to find out the effect of the Index Card Match strategy in mufradat learning on the Arabic language learning outcomes of fourth grade students at Madarasah Ibtidaiyah Negeri 1 Sidoarjo. Design/Methodology/Approach- This research uses Classroom Action Research (CAR) with a model developed by Stephen Kemmis which consists of 5 stages, namely finding the focus of the problem, planning actions, implementing actions, observing/collecting data, and reflecting. This research data collection uses observation, test, and documentation techniques. Meanwhile, the data analysis of this research used a qualitative approach and a quantitative approach. Findings- The results of this study indicate that: The implementation of the Index Card Match strategy on ta'aruf material for class IV C students of Madrasah Ibtidaiyah Negeri 1 Sidoarjo has been implemented well. This can be seen from the results of observations that teacher activities have increased, in the first cycle the score is 63.20, in the second cycle the score is 86.40. Meanwhile, the results of the observation of student activities also increased, in the first cycle the score was 60.00 and in the second cycle the score was 76.80. The implementation of the Index Card Match strategy in Arabic learning has increased, the percentage of learning outcomes in the pre-cycle only reached 20% with an average value of 46.33. In the first cycle, the achievement of learning completeness reached 60% with an average value of 58.03 students. In the second cycle, mastery learning increased to 86.66% with an average value of 74.00.